The well-grounded Rubyist - Black, David A.; Leo, Joseph (Manning Publications Co., 2019)
In The Well-Grounded Rubyist, Third Edition expert authors David A. Black and Joseph Leo deliver Ruby mastery in an easy-to-read, casual style. You'll lock in core principles as you write your first Ruby programs. Then, you'll progressively build up to topics like reflection, threading, and recursion, cementing your knowledge with high-value exercises to practice your skills along the way.